Metabolic mechanisms of immunotherapy resistance - Luis Cabezón-Gutiérrez; Magda Palka-Kotlowska; Sara Custodio-Cabello; Beatriz Chacón-Ovejero; Vilma Pacheco-Barcia (Exploration of Targeted Anti-tumor Therapy)
Immunotherapy has revolutionized cancer treatment, yet its efficacy is frequently compromised by metabolic mechanisms that drive resistance. Understanding how tumor metabolism shapes the immune microenvironment is essential for developing effective therapeutic strategies. This review examines key metabolic pathways influencing immunotherapy resistance, including glucose, lipid, and amino acid metabolism. We discuss their impact on immune cell function and tumor progression, highlighting emerging therapeutic strategies to counteract these effects. Tumor cells undergo metabolic reprogramming to sustain proliferation, altering the availability of essential nutrients and generating toxic byproducts that impair cytotoxic T lymphocytes (CTLs) and natural killer (NK) cell activity. The accumulation of lactate, deregulated lipid metabolism, and amino acid depletion contribute to an immunosuppressive tumor microenvironment (TME). Targeting metabolic pathways, such as inhibiting glycolysis, modulating lipid metabolism, and restoring amino acid balance, has shown promise in enhancing immunotherapy response. Addressing metabolic barriers is crucial to overcoming immunotherapy resistance. Integrating metabolic-targeted therapies with immune checkpoint inhibitors may improve clinical outcomes. Future research should focus on personalized strategies to optimize metabolic interventions and enhance antitumor immunity.